A re-evaluation of manner of death at Roman Herculaneum following the AD 79 eruption of Vesuvius. (February 2020) - Martyn, Rachelle; Craig, Oliver E.; Ellingham, Sarah T.D.; Islam, Meez; Fattore, Luciano; Sperduti, Alessandra; Bondioli, Luca; Thompson, Tim
Abstract: Abstract : Destroyed by the eruption of Mount Vesuvius in AD 79, Herculaneum is one of the world's most famous Roman settlements. Exactly how the victims died during the eruption, however, remains unclear. The authors address this issue by examining changes in bone apatite structure and collagen preservation, combined with collagen extraction. Results suggest that the prolonged presence of soft tissue, as well as the stone chambers in which inhabitants had sought shelter, acted as thermal buffers that minimised the heat-induced degradation of skeletal tissues. The results have implications for the interpretation of large residential sites and for contexts where heating and burning is associated with buildings.